Tanggung Jawab Pengelola Terhadap Kerugian Pengunjung Taman Wisata Embung Desa Di Desa Padang Jaya Kabupaten Bengkulu Utara - Husnah, Riska Saifatul; Arso, Dimas Dwi; Sofyan, Tito (Jurnal Ilmiah Kutei, 2022)
Business actors in the tourism sector are competing to provide tourist attractions, ranging from tourist attractions that utilize nature and artificial tourism objects. One of the tourist attractions in Padang Jaya Village is the Village Embung Tourism Park. The basis for the implementation of tourism activities is regulated in Law Number 10 of 2009 concerning Tourism. In tourism activities, legal aspects sometimes tend to be ignored in the processing of the tourism business, especially in tourism business businesses which are mostly held conventionally. This study aims to find out and analyze the form of responsibility of the manager for the loss of visitors to the Embung Desa tourist park and the application of the manager's obligations based on Article 26 letter (d) of Law Number 10 of 2009 concerning Tourism. The research methods used in this study are empirical legal research and empirical or sociological legal approaches. The form of responsibility given by the manager is in the form of providing first aid and providing medical expenses to visitors who have suffered losses. Internal factors hinder the implementation of Article 26 letter (d) of Law Number 10 of 2009 concerning Tourism are because the managers and workers are not firm and disciplined in carrying out supervision. External factors that are hindering are due to the legal culture of the community and there are no detailed provisions regarding the limitations of the criteria for comfort, friendliness, protection of security and safety of visitors.